Assessment of Nurses’ Knowledge toward Sleeve Gastrectomy in Surgical Unit at Al-Najaf Al-Ashraf Governorate - Hadeel Abbass Wadi Al-Azawi; Dergham Majjed Hameed (Institute of Medico-legal Publications Pvt Ltd, 2021)
A sleeve gastrectomy is a life changing surgery which used for helping patients who are severing fromobesity (BMI 40+ or BMI 35+ with other health problems) for losing weight and enhance their health weightloss help to less the risk for development medical conditions related to obesity as high blood pressure,D.M, arthritis, respiration problems), the sleeve gastrectomy operation makes stomach small to changethe amount of meals, and it helps to losing weight. This study aims to assess nurses’ knowledge towardquantification sleeve gastrostomy in surgical unit and to identify the relationship between nurses’ knowledgeabout quantification sleeve gastrostomy and their sociodemographic data in surgical unit. A quantitativedescriptive design is used in the present study to perform objectives. A purposive sampling method; 40nurses distributed on hospitals in surgical units, the data collection used through constructed questionsdivided to demographic data and nurses’ knowledge, and data analyzed by descriptive analysis and anInferential analysis. Nurses’ knowledge about sleeve gastrostomy was ranging between poor to moderate,and as general the total score of nurses’ knowledge was poor and no significant association between nurses’knowledge and their demographic characteristics.